Comparing Subsurface Seasonal Deoxygenation and Acidification in the Yellow Sea and Northern East China Sea Along the North-to-South Latitude Gradient - Xiong, Tian-qi; Wei, Qin-sheng; Zhai, Wei-dong; Li, Cheng-long; Wang, Song-yin; Zhang, Yi-xing; Liu, Shuo-jiang; Yu, Si-qing (Frontiers in Marine Science, 2020)
To better understand the relationship between subsurface seasonal deoxygenation and acidification in the Yellow Sea and northern East China Sea (ECS), we examined carbonate system parameters and dissolved oxygen (DO) of seven field surveys conducted in 2017–2018, spanning all four seasons. Low pHT values of 7.71‒7.80 and critically low aragonite saturation state (Ωarag) values of 1.07‒1.40 along with undersaturated DO of mostly higher than 150 μmol O2 kg–1 occurred in the Yellow Sea Cold Water Mass area in summer and autumn, while hypoxic DO values of 49‒63 μmol O2 kg–1 and extremely low pHT values of 7.68‒7.74 as well as critically low Ωarag values of 1.21‒1.39 were observed in the northern ECS in July 2018. At the beginning of warm-season stratification formation, the cold Yellow Sea waters had much higher DO but lower Ωarag values than those in relatively warmer ECS waters, while yearly initial pHT values rarely exhibited differences between the two coastal seas. During warm seasons, the central Yellow Sea accumulated respiration products beneath the thermocline in summer and autumn, while the northern ECS bottom waters preserved them only in summer. This study highlights fundamental roles of wintertime carbon dioxide (CO2) solubility along a north-to-south latitude gradient in the coastal acidification development. In comparison with the relatively low-latitude northern ECS subject to seasonal hypoxia, relatively high-latitude Yellow Sea exhibits higher CO2 solubility in winter and longer respiration-product accumulations in warm seasons, leading to lower Ωarag in the central Yellow Sea than those in the northern ECS. However, the present-day central Yellow Sea is free from hypoxia.